2020
DOI: 10.15561/20755279.2020.0104
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity of the university's senior students

Abstract: Background and Study Aim. To prevent hypodynamics, to evaluate the volume and level of weekly physical activity of the university's senior students. Material and methods. The study involved students (n = 244) aged 19-20 years (n = 157 - boys, n = 87 - girls). The students studied in the 4th year of the Technical University (Russia). The following parameters were investigated: physical activity (PA), the intensity of metabolic processes and motor skills. The volume of weekly physical activity was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Among the limitations that were concluded from the findings are less sample size, the potential of bias, or reporting of the physical activity level contributing to the overestimation, and the analysis was not performed according to different areas. Moreover, the COVID-19 pandemic could have led to less physical activity as universities were closed as a measure of prevention of COVID-19 infections, limiting access to sports areas and training sessions (Kolokoltsev & Jagiello, 2020). Furthermore, the study reveals that in the investigation, there were more females than males.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Among the limitations that were concluded from the findings are less sample size, the potential of bias, or reporting of the physical activity level contributing to the overestimation, and the analysis was not performed according to different areas. Moreover, the COVID-19 pandemic could have led to less physical activity as universities were closed as a measure of prevention of COVID-19 infections, limiting access to sports areas and training sessions (Kolokoltsev & Jagiello, 2020). Furthermore, the study reveals that in the investigation, there were more females than males.…”
Section: Discussionmentioning
confidence: 90%
“…Analysis had shown that the total physical activity of males was significantly higher than females and FSR was significantly higher than FBM. This can be due to the reason that FSR students tend to perform physical activity with moderate to vigorous intensity as part of their daily routines (Kolokoltsev & Jagiello, 2020). The maximum weekly volume of PA of female students was slightly more than 3000 minutes (Osipov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, physical activity can be defined as body movements triggered by skeletal muscle contractions, which in turn produce energy or power. It is important to note that physical activity is not limited to sports activities only, but also includes daily routines such as going to work, going to school, or other activities that involve body movement (Kolokoltsev and Jagiello, 2020). Physical activity has an important influence on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Kolokoltsev & Jagiello evaluated the weekly physical activity level of fourth-year students at the Technical University of Russia. They found that 23.4% of the students had low levels of physical activity and motor skills, indicating a tendency of young students to lack movement, which is a sign of the risk of developing chronic diseases in the body [18].…”
Section: Introductionmentioning
confidence: 99%